2021
DOI: 10.1111/trf.16272
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion management for children supported by extracorporeal membrane oxygenation

Abstract: Ideas • Due to the patients' underlying illness, in combination with circuit-induced coagulopathy, as well as PLT dysfunction, children supported by ECMO are a risk of receiving large volumes of blood components. • Given the increasing use of modified blood products and newer biologics, it is unknown whether these products have equal efficacy and safety, in ECMO. • The majority of guidance for transfusion therapy is based on expert opinion alone, and research on indications for RBC, plasma, and PLT transfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Therefore, sputum, mucus, pus, plasma, serous fluid and some other colloidal tissues remain inside the airways, impair gas exchange and blood oxygenation [58,118]. Under these conditions, today it is possible to increase blood oxygen saturation only by extracorporeal membrane oxygenation (ECMO) [119][120][121][122]. But ECMO is inaccessible to most patients, because it many times increases the cost of COVID-19 treatment, as well as carries death itself to half of patients with COVID-19 [58,123].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, sputum, mucus, pus, plasma, serous fluid and some other colloidal tissues remain inside the airways, impair gas exchange and blood oxygenation [58,118]. Under these conditions, today it is possible to increase blood oxygen saturation only by extracorporeal membrane oxygenation (ECMO) [119][120][121][122]. But ECMO is inaccessible to most patients, because it many times increases the cost of COVID-19 treatment, as well as carries death itself to half of patients with COVID-19 [58,123].…”
Section: Resultsmentioning
confidence: 99%
“…Many infants with these hemorrhagic complications are treated with FFP and/or cryoprecipitate. [85][86][87][88][89] Neonates undergoing treatment with ECMO have had a higher frequency of intracranial hemorrhage when they had low fibrinogen levels. 90,91 The ELSO guidelines advise for transfusion of plasma or cryoprecipitate to maintain fibrinogen levels above 150 mg/dL.…”
Section: Use O F Cryoprecipitate I N Acquired Coagulation Disordersmentioning
confidence: 99%
“…A growing appreciation for transfusion practices and mortality on ECMO has led many centers to adjust transfusion practices in an effort to lower blood product exposure. 9 These new practices appear to be safe with comparable complication rates. 4,[10][11][12] Limited studies in neonates have demonstrated similar outcomes with lower transfusion thresholds during ECMO.…”
Section: Introductionmentioning
confidence: 97%
“…Neonates undergoing ECMO support are an ideal population to investigate the relationship between mortality and transfusions on ECMO as they represent a relatively homogenous population with limited indications for ECMO and few antecedent comorbidities prior to ECMO initiation. A growing appreciation for transfusion practices and mortality on ECMO has led many centers to adjust transfusion practices in an effort to lower blood product exposure 9 . These new practices appear to be safe with comparable complication rates 4,10–12 .…”
Section: Introductionmentioning
confidence: 99%